Strategi Pemasaran Susu Kambing Di Bogor: Marketing Strategy of Goat Milk in Bogor - Lalita Paraduhita Martha; Ma’mun Sarma; Mukhamad Najib (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2016)
Milk consumption enhancement that not matched the number of domestic supply which still rely on cow’s milk makes Indonesia continue to importing milk, almost 70 percent of the total needed. An alternative to the fulfilment is to increase the supply from other livestock such as dairy goats. Bogor is a potential area for the development of dairy goat farm. The aims of this research are to: 1) analyze the goat's milk business potency in Bogor which considering the internal and external factors; and 2) develop an effective marketing strategy in order to improve the goat milk business in Bogor. The data was used in this research are primary and secondary data. The interviews for data collection conducted on October 2014 through November 2016, using a questionnaire tools with Strengths-Weaknesses-Opportunities-Threats (SWOT) and Analytical Hierarchy Process (AHP) approach. The research respondents amounted to 9 for SWOT and 7 to AHP. The respondents located in Bogor consisted of academics, dairy goat breeders, goat's milk seller/agent, agricultural bureau of the city also animal husbandry bureau and fisheries of the district. The internal factor has score of 2.701 of goat milk business in the city and district of Bogor, while the external factor has score of 3.085. Merging the two matrices put goat’s milk business into cell II, that is the grow and build cells. The recommendation of key strategic for goat’s milk marketing which effective based on the results of AHP with score of 0.202 is to make the development of goat’s milk business as part of government road map as an effort to optimize the potential of the city and district of Bogor.